1994
DOI: 10.7863/jum.1994.13.8.607
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar vermian defects: antenatal sonographic appearance and clinical significance.

Abstract: A partial or complete defect of the cerebellar vermis may occur sporadically or as a component of the Dandy-Walker syndrome, the Dandy-Walker variant, Down's syndrome, or Joubert-syndrome. We identified a defect of the cerebellar vermis in nine fetuses on routine antenatal sonographic studies. In five of the nine fetuses other abnormalities, including central nervous system and non-central nervous system lesions were identified. Three of these five fetuses died and two infants have remained well on follow-up. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 6 publications
1
18
0
1
Order By: Relevance
“…Isolated inferior vermian defect was reported to be associated with a good prognosis (2). Obstetric management and also the neonatal outcome depends on the gestational age at diagnosis, karyotype analysis and associated intracranial or extracranial abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolated inferior vermian defect was reported to be associated with a good prognosis (2). Obstetric management and also the neonatal outcome depends on the gestational age at diagnosis, karyotype analysis and associated intracranial or extracranial abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…A partial or complete cerebellar vermian defect may occur sporadically or as a component of the Dandy-Walker syndrome (DWS), Down syndrome or Joubert Syndrome (2). The Dandy-Walker malformation (DWM), Dandy-Walker variant (DWV), and mega cisterna magna (MCM) seem to represent steps on a continuum of developmental anomalies of the posterior fossa (3).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to DWM and its variant, arachnoid cyst is generally associated with favorable outcome after decompression of the cyst by cystoperitoneal shunting or fenestration. [14][15][16][17][18][19][20][21][22] Isolated MCM has been associated with normal pregnancy and neonatal outcome. 23 One recent study has shown prenatal ultrasonographic diagnosis of central nervous system anomalies to have a high concordance with the autopsy diagnosis (89%).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of the lower lobe of the vermis creates the "keyhole" observed ultrasonographically which is very useful in DWV diagnosis (Fig. 4) [12,13].…”
Section: Keyhole Sign (Dandy-walker Malformation)mentioning
confidence: 99%